Glaciological Survey in the Bare Ice Area near the Allan Hills in Victoria Land, Antarctica - Nishio, Fumihiko; Annexstad, John O. (1979)
P(論文) During the 1978-1979 field season, the third U. S.-Japan joint program entitled "Antarctic search for meteorites" was carried out on the plateau side of the Allan Hills in South Victoria Land. This program included a glaciological study to elucidate the mechanism of accumulation of a large number of meteorites in the bare ice area. In December 1978,a triangulation chain with 20 stations, 15km in length, was newly established in the Allan Hills bare ice field to investigate the ice flow. Values of elevation and coordinates (X, Y) of all stations are tabulated. The error in elevation of farthest station from the datum point is ±7cm, and errors in position of the same station are ±0.932m in X coordinate and ±1.128m in Y coordinate. The extensive bare ice area on the ice sheet surface in the vicinity of the Allan Hills is located upstream of the mountain range, and the bare ice fields inland west to the plateau of the East Antarctic ice sheet are located in the neighborhood of a sub-ice bedrock mountain. Therefore, the ice flow coming down towards the Allan Hills or into the Mawson Glacier should be forced to make an upward movement in the neighborhood of the mountains. departmental bulletin paper